(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Ciro Guerra’s The Wanderer’s Shadow (2004), Oscar Campo’s I Am Another (2008) and Alejandro Landes’s Porfirio (2012) are three contemporary films representative of a recent tendency towards a less “direct” representation of the Colombian armed conflict than that which may be found in previous political filmic production. This article proposes that the relation between these films and the armed conflict may be understood, not in terms of representation, but through the concept of mediation. Fundamental to the films’ mediatory function is the production of affects that persist beyond the spectator’s viewing experience. In this sense, the agency of these films in relation to the conflict consists, not in directly informing its history or memory but in the production of the affective motivation necessary to undertake the construction of said memory.